Analysis of Human Resources Development on Civil Servant Career Development at the Mining and Energy Department of Fakfak Regency - Agustina Waromi; Thaib Wasaraka; Semuel Rumaropen (Budapest International Research and Critics University, 2022)
The development of human resources, whether working in the public sector as civil servants, employees of State-Owned Enterprises (BUMN), as employees of Regional-Owned Enterprises (BUMD), and the private sector, needs to be carried out in a planned and sustainable manner. In order for human resource development (HR) to be carried out properly, a human resource development program must first be established. The research method is qualitative. The results of the study show that the on-the-job training method includes all efforts to train civil servants in the real workplace. Civil servants do real work, not simulated tasks. Civil servants receive various instructions from senior civil servants who are experienced in their work. The training is carried out in a real work environment under normal conditions and does not require special training facilities. Conclusion The internship program is designed for higher skill levels. This internship program leads to education rather than training called human resource development, in this case knowledge in doing a skill or a series of interconnected jobs. Internship provides employees with various experiences in certain jobs, and or an introduction to the work of the organization or industry. Internships provide civil servants with a wide range of experience at a relatively low cost to an organization.